CONTAINER DAN RUMAH POSITIF JENTIK NYAMUK AEDES AEGYPTI TERHADAP KEJADIAN DEMAM BERDARAH DENGUE - Theodorus Teddy Bambang Soedjadi; Risnawati Tanjung; Deli Syaputri; Samuel Marganda Halomoan Manalu (Poltekkes Kemenkes Medan, 2022)
Dengue Hemorrhagic Fever (DHF) is one of the environmental health problems that tends to increase in the number of sufferers and the wider the area of ??distribution, in line with increasing mobility and population density. In Indonesia, Dengue Hemorrhagic Fever (DHF) has been recognized since 1968 in Surabaya and Jakarta. The presence of Aedes aegypti larvae in an area is an indicator of the presence of Aedes aegypti mosquito populations in that area. Environmental conditions are one of the conditions that can affect the development of mosquito larvae. Based on data from the Toba Samosir District Health Office, the incidence of dengue fever in Toba Samosir Regency continues to increase from year to year. In 2012 there were 24 cases. In 2013 and 2014 it increased to 25 cases and 51 cases. Then in 2015 it increased again to 77 cases. Data in 2016 and 2017 increased sharply to 110 cases and 129 cases. Throughout 2012 to 2017, In January to June 2018 there were 49 cases and Balige District became the highest data contributor. The purpose of this study was to determine the relationship between containers and houses positive for Aedes aegypti mosquito larvae with the incidence of dengue hemorrhagic fever (DHF) in Toba Samosir Regency. Observational study with a case control design with a ratio of 1:1 (49 cases and 49 controls). The statistical test used is Chi-Square. The results of the bivariate analysis showed that the container inside the house was larva positive, the container outside the house was larva positive, and the house was larva positive were risk factors for the incidence of DHF. For this reason, it is necessary to implement PSN in the form of 3M (draining, burying, and planting things).